Competency of the liturgy of the word and preaching for the management of the Parish Church of ST. Damian, Lau Baleng Tanah Karo - Paulus, Paulus Halek Bere; Paulinus Tibo; Dewiana Lase; Anugrah Steven Doloksaribu; Adela Cristina br Sembiring (Educenter : Jurnal Ilmiah Pendidikan, 2025)
The Liturgy of the Word serves to strengthen faith, shape congregational identity, and transform congregational life. Meanwhile, preaching, as part of the Liturgy of the Word, has a sacramental dimension and functions to renew the Word of God in the context of people's lives. The purpose of this study is to analyze the competence of church administrators in delivering the Liturgy of the Word and sermons, explore contextual challenges in its implementation in the midst of congregations without priests, and formulate strategies for empowering liturgy and homilies based on local culture as a relevant and sustainable pastoral solution. The approach used in this research is participatory action research. Data collection techniques include observation, interviews, and documentation. The results showed that in St. Damian Parish, Lau Baleng, there is a competency gap among church administrators in the understanding and animation of the Liturgy of the Word as well as preaching skills. The quality of service, including the abilities to inculturate the liturgy in Karo culture, requires structured training. A pastoral approach in liturgy is key to creating meaningful experiences for the people, especially in a multicultural context.